Justice League of America : power and glory - Hitch, Bryan; Bedard, Tony (DC Comics, 2017)
"Bryan Hitch makes his triumphant return to DC Entertainment with the world's most powerful heroes, the JUSTICE LEAGUE OF AMERICA! It's massive widescreen action and adventure from superstar writer/artist Hitch, as the League comes up against an armada ofaliens heading for Earth that claims to be a peaceful religious tribe. But something sinister is lurking in their ranks...something with ties to ancient Krypton! And more importantly...whose side will the Man of Steel fall on?"--